2013
DOI: 10.1124/jpet.113.204206
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-Dependent Inhibition of Human MATE1 by Cationic Ionic Liquids

Abstract: The multidrug and toxin extruders 1-and 2-K (MATE1 and MATE2-K) are expressed in the luminal membrane of renal proximal tubule cells and provide the active step in the secretion of molecules that carry a net positive charge at physiologic pH, so-called organic cations. The present study tested whether structurally distinct MATE substrates can display different quantitative profiles of inhibition when interacting with structurally distinct ligands. The tested ligands were three structurally similar cationic ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…The two screens of inhibitor interaction with MATE1 reported to date focused on profiles generated against transport of single substrates, i.e., MPP (Astorga et al, 2012) or ASP (Wittwer et al, 2013). However, we did recently report that two structurally distinct ionic liquids (1-methyl-3-butylimidazolium and N-butyl-N-methylpyrrolidinium) had IC 50 values for inhibition of MATE1-mediated transport of [ 3 H]MPP that were about 4-fold lower than the values observed for inhibition of transport of [ 3 H]-triethylmonomethylammonium, consistent with the concept of substrate-dependent ligand interaction with MATE transporters (Martínez-Guerrero and Wright, 2013). However, the current results suggest that substrate identity exerts comparatively little influence on ligand interaction with MATE1.…”
Section: Discussionsupporting
confidence: 78%
“…The two screens of inhibitor interaction with MATE1 reported to date focused on profiles generated against transport of single substrates, i.e., MPP (Astorga et al, 2012) or ASP (Wittwer et al, 2013). However, we did recently report that two structurally distinct ionic liquids (1-methyl-3-butylimidazolium and N-butyl-N-methylpyrrolidinium) had IC 50 values for inhibition of MATE1-mediated transport of [ 3 H]MPP that were about 4-fold lower than the values observed for inhibition of transport of [ 3 H]-triethylmonomethylammonium, consistent with the concept of substrate-dependent ligand interaction with MATE transporters (Martínez-Guerrero and Wright, 2013). However, the current results suggest that substrate identity exerts comparatively little influence on ligand interaction with MATE1.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, previous reports demonstrated that imatinib inhibited OCT1-mediated metformin uptake with an IC 50 value of 1.5 mM (Minematsu and Giacomini, 2011), whereas in our study imatinib inhibited serotonin uptake with an IC 50 value of 10.2 mM. This confirms the substrate-dependent inhibition seen with other organic cation transporters (Belzer et al, 2013;Martínez-Guerrero and Wright, 2013) and suggests that these transporters have complex binding pockets, with different interaction sites for different substrates. Regardless, these novel results are strong evidence that xenobiotics may inhibit serotonin uptake in the liver, potentially hindering proper hepatic clearance of serotonin in vivo, and it is plausible that these same effects would be seen with other endogenous substrates as well.…”
Section: Discussionsupporting
confidence: 53%
“…Inhibition of OCT1-related transport of dopamine by the two pyrethroids was however rather less marked than that of DAPI; indeed, allethrin used at 10 μM reduced OCT1-mediated DAPI and dopamine accumulation by 73.7% and 51.6%, respectively, whereas 10 μM tetramethrin decreased DAPI uptake by 66.4%, but failed to significantly alter that of dopamine (S7B Fig and Fig 5). This likely illustrates the fact that inhibitory profiles for a transporter can vary according to the nature of the substrate and of drug binding sites, as already established for various transporters, including organic cation transporters [67–69]. The mechanism by which pyrethroids like allethrin and tetramethrin down-regulate OCT1 activity remain to be determined.…”
Section: Discussionmentioning
confidence: 70%